2017
DOI: 10.14348/molcells.2017.2278
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Central NELL2 in the Regulation of Feeding Behavior in Rats

Abstract: A brain-enriched secreting signal peptide, NELL2, has been suggested to play multiple roles in the development, survival, and activity of neurons in mammal. We investigated here a possible involvement of central NELL2 in regulating feeding behavior and metabolism. In situ hybridization and an im-munohistochemical approach were used to determine expression of NELL2 as well as its colocalization with proopiomelanocortin (POMC) and neuropeptide Y (NPY) in the rat hypothalamus. To investigate the effect of NELL2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…investigated NELL2‐regulated feeding behavior. A block of NELL2 production led to a decrease in daily food intake followed by a loss in body weight (Jeong et al., 2017). According to the parents’ report, our patient showed feeding difficulties in the first 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…investigated NELL2‐regulated feeding behavior. A block of NELL2 production led to a decrease in daily food intake followed by a loss in body weight (Jeong et al., 2017). According to the parents’ report, our patient showed feeding difficulties in the first 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed in this study that mRNA level of NELL2 expression in the hypothalamus was elevated during fasting, when compared to a fed state. Therefore, it is likely that central NELL2 is responsible for an orexigenic mechanism in rodents.Anatomical verification revealed that NELL2 is produced both in neuropeptide Y (NPY) and proopiomelanocortin (POMC) cells in the ARC, both of which are critical in metabolism regulation through functional opposition [7]. Therefore, we also investigated whether NELL2 signaling is associated with gene expression of NPY and POMC.…”
mentioning
confidence: 99%
“…Although NELL2 is broadly distributed throughout the mammalian brain, we previously reported that its expression is brain region-specific and cell type-dependent [5]. Importantly, NELL2 is produced relatively high in the hypothalamus compared to other brain regions [5,7]. In addition, core hypothalamic nuclei known to play a critical role in metabolism regulation, such as the paraventricular nucleus, ventromedial nucleus, and the arcuate nucleus of the hypothalamus (ARC) are also a main site of NELL2 production [5,7].…”
mentioning
confidence: 99%
See 2 more Smart Citations